Sosialisasi dan Edukasi Investasi dan Portofolio Pasar Modal di SMA Negeri 2 Bengkalis Riau - Imam Fakhruddin; Firdaus, Firdaus; Arini, Siti; Nanda Wiyah, Qhoriatul; Gatot Prasetiyo, Nugroho (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The socialization and education on investment and capital market portfolios at SMA Negeri 2 Bengkalis, Riau, is motivated by the lack of basic knowledge about the capital market among students, which can hinder their ability to make smart financial decisions in the future. This activity aims to provide comprehensive information about investments, portfolio management, and the importance of financial planning. The purpose of this socialization is to introduce students to various investment instruments such as stocks, bonds, and mutual funds, as well as techniques for analyzing risks and potential returns. This activity also aims to equip students with practical skills in managing their own portfolios. The methods used include presentations by capital market experts, Q&A sessions, and investment simulations. This approach is designed to actively engage students and provide hands-on experience in the world of investing. The expected outcomes include an increase in students' knowledge about investments and capital markets, the ability to make better investment decisions, and an awareness of the importance of personal financial planning.